2017
DOI: 10.1080/10717544.2017.1324531
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone distribution characteristic following controllable continuous sub-tenon drug delivery in rabbit

Abstract: Drug delivery systems are required to be safe, minimally invasive and effectively delivery drug to the target tissues. But delivery drugs to the eye has not yet satisfied this need. Here, we focused on examining the distribution of dexamethasone (DEX) in ocular and plasmic samples following controllable continuous sub-Tenon drug delivery (CCSDD) of dexamethasone disodium phosphate (DEXP) in rabbit, and to compare that with two traditional routes: subconjunctival injection and intravenous injection. The DEX con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…[5] It was reported that subconjunctival injection of hydrophobic drugs could provide the highest drug concentration in sclera, then in retina/choroid and cornea, followed by in iris, plasma, aqueous, lens, and vitreous in order. [24] And subconjunctival administration could present a higher drug concentration in eye tissues, while only obtain a lower drug concentration in the systemic circulation through the conjunctival blood and lymphatic vessels. The systemic drug distribution after a subconjunctival administration is negligible.…”
Section: In Vivo Inhibition Effectivenessmentioning
confidence: 99%
“…[5] It was reported that subconjunctival injection of hydrophobic drugs could provide the highest drug concentration in sclera, then in retina/choroid and cornea, followed by in iris, plasma, aqueous, lens, and vitreous in order. [24] And subconjunctival administration could present a higher drug concentration in eye tissues, while only obtain a lower drug concentration in the systemic circulation through the conjunctival blood and lymphatic vessels. The systemic drug distribution after a subconjunctival administration is negligible.…”
Section: In Vivo Inhibition Effectivenessmentioning
confidence: 99%
“…Dexamethasone also cause diabetes related complications, immune suppressor and cause hypertension. Poor gastrointestinal stability, low bioavailability, poor transport behavior and side effect on other organs like kidney limit its therapeutic effectivity ( Alessi et al, 2020 ; Huang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%